Exploring the relationship between motor development and entrepreneurial traits in childhood - Inês Peixoto Silva; Beatriz Pereira (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Children’s motor development is growing, with several studies seeking to understand its process, causes, and effects. The field of entrepreneurship has also experienced significant growth.  Objective: Recognizing the importance of both areas, this research aims to verify the relationship between a child's motor development and entrepreneurial traits.  Methodology: This is an exploratory case study using mixed methodologies. 37 students from the 1st and 3rd grade participated in this study. The Test of Gross Motor Development - 2 was used to determine the children's motor development. To assess entrepreneurial traits in children, observation and audio recording were conducted in three contexts: structured play, enriched recess, and storytelling. The observation was based on a script constructed according to the literature review.  Results: When relating motor development to entrepreneurial traits, it was concluded that children with better motor development in the total raw score and object control motor skills tend to be those in the 3rd grade and those with lower propensity for inverse behaviour of "Self-Confidence" and "Persistence/Resistance to Failure." It was also found that children with better raw scores in locomotion motor skills are also those who, in the context of recess, have a greater tendency to exhibit positive behaviour of "Risk-taking," such as considering risks before acting or not being afraid of failure. Conclusion: Schools should integrate entrepreneurial education and motor skill development into curricula to prepare students not just for jobs, but to take initiative, solve complex problems, and adapt to changing circumstances throughout their lives.